BATASAN KEBEBASAN BERPENDAPAT MELALUI MEDIA ELEKTRONIK DALAM PERSPEKTIF HAM DIKAITKAN DENGAN TINDAK PIDANA MENURUT UU ITE - Fadilah Raskasih (JOURNAL EQUITABLE, 2020)
This study aims to determine the limitations of freedom of expression through electronic media viewed from the perspective of Human Rights associated with criminal acts, and to recognize the ideal arrangement of freedom of expression limitations through electronic media. This study uses a doctrinal type of research. The results of the study show that the Human Rights and the prevailing laws and regulations relating to freedom of expression, must be balanced. So the current regulations regarding the freedom of expression are deemed necessary. However, it requires a more detailed explanation concerning several categories that are considered as violations of Human Rights against others.